2020
DOI: 10.1186/s12889-020-08753-y
|View full text |Cite
|
Sign up to set email alerts
|

The quadrivalent HPV vaccine is protective against genital warts: a meta-analysis

Abstract: Background: The quadrivalent human papillomavirus (HPV) vaccine has been assumed to give protection against genital warts (GW) as well as cervical cancer. Our main question was whether HPV vaccine has any effects on the prevention of GW reported in randomised controlled clinical trials (RCTs) and time-trend analyses. Methods: This meta-analysis was performed according to the PRISMA guidelines using the PICO format. We searched in three electronic databases (PubMed, Embase, Cochrane Trials), and assessed hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Most vaccinations given in 2014 were the quadrivalent type, which targets oncogenic HPV types 6/11/16/18. The quadrivalent HPV vaccine shows excellent efficacy against genital warts in young women (pooled OR = 0.36; 95% CI = 0.26 to 0.51) and young male (pooled OR = 0.69; 95% CI = 0.61 to 0.78) [50]. The vaccine efficacy in an unrestricted susceptible population (USP) (negative polymerase chain reaction (PCR) and serologic testing at enrollment) was 100% (95% CI = 94% to100%) against the four HPV subtypes 3 years after vaccination.…”
Section: Efficacy and Effectiveness Of The Hpv Vaccine In Young Women...mentioning
confidence: 99%
“…Most vaccinations given in 2014 were the quadrivalent type, which targets oncogenic HPV types 6/11/16/18. The quadrivalent HPV vaccine shows excellent efficacy against genital warts in young women (pooled OR = 0.36; 95% CI = 0.26 to 0.51) and young male (pooled OR = 0.69; 95% CI = 0.61 to 0.78) [50]. The vaccine efficacy in an unrestricted susceptible population (USP) (negative polymerase chain reaction (PCR) and serologic testing at enrollment) was 100% (95% CI = 94% to100%) against the four HPV subtypes 3 years after vaccination.…”
Section: Efficacy and Effectiveness Of The Hpv Vaccine In Young Women...mentioning
confidence: 99%
“…The Advisory Committee on Immunization Practices recommends vaccinating all MSM up through age of 26 years due to the increased risk of anal cancer in this key population [21] A recent meta-analysis [22] has reported the average HPV vaccine acceptability among MSM of 63% with the highest from China (97%) [23] and the lowest from Australia (30%) [24], however an increasing trend of vaccine uptake is being reported by others over time [25]. Studies have reported decline in HPV associated anogenital warts among MSM since the introduction of HPV vaccination program [26,27]. Furthermore, anal Papanicolaou (Pap) screening for the precancerous HPV anal lesions as a secondary prevention may have greater utility in preventing future anal cancer [28][29][30][31] and indeed is a cost-effective method for anal cancer prevention among MSM [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast and coherently to what was reported in other countries, Genital Warts, caused by the papillomavirus, showed a slight decrease over time [ 30 ]. This is a reduction that could most likely be a direct and visible effect of the mass HPV vaccination strategy adopted in our country along with many other countries in Europe [ 40 , 41 , 42 , 43 , 44 , 45 ], which deserves further investigation.…”
Section: Discussionmentioning
confidence: 87%